No Apparent Workup for most new Indeterminate Pulmonary Nodules in US Commercially-Insured Patients - Bruce S. Pyenson; Carol M. Bazell; Michael J. Bellanich; Melissa A. Caplen; Javier J. Zulueta (Journal of Health Economics and Outcomes Research)
# Background A recent study estimated that more than 1.5 million Americans have an indeterminate pulmonary nodule (IPN) identified on a chest computed tomography (CT) scan each year outside of lung cancer screening programs. However, the cost and pattern of subsequent IPN workup have not been described for real-world settings.